A time-delay-integration CMOS image sensor with pipelined charge transfer architecture - Yu, Hang (2013)
In this paper, we report a novel Time-Delay-Integration (TDI) CMOS image sensor for low-earth orbit (LEO) nano-satellite imaging application, where limited exposure time and unexpected flight fluctuations are major design challenges. The sensor features programmable integration time per stage, dynamic charge transfer path and tunable well capacity. A prototype chip of 1536×8 pixels was implemented using TSMC 0.18µm CMOS image sensor process. Photodiode and other transistors are floor-planned in different arrays, providing small pixel pitch of 3.25µm and high fill factor of 57%.